Thursday, 14 June 2018: 2018
DOI: 10.1136/annrheumdis-2018-eular.2947
|View full text |Cite
|
Sign up to set email alerts
|

THU0330 Obesity in psoriatic arthritis: comparative prevalence with skin psoriasis and associated factors

Abstract: BackgroundObesity (BMI ≥30 kg/m2) is a common cardiovascular risk factor in psoriatic disease1. Although the prevalence of obesity is high, the factors associated with it in psoriatic arthritis (PsA) are poorly understood.ObjectivesWe aimed to evaluate the prevalence and obesity-associated factors in patients with PsA.MethodsRetrospective cross-sectional study that included 205 consecutive patients with PsA according to CASPAR criteria. The prevalence of obesity was compared with that of 310 patients with skin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
13
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 0 publications
1
13
1
Order By: Relevance
“…PsA is a chronic inflammatory arthritis burdened by a series of metabolic comorbidities. Among them, obesity is very common in PsA, with a prevalence of 27%, as confirmed by a recent Spanish work 2. Obesity in PsA has been associated with higher disease activity and a worse effectiveness of biologic treatment in PsA.…”
mentioning
confidence: 75%
See 2 more Smart Citations
“…PsA is a chronic inflammatory arthritis burdened by a series of metabolic comorbidities. Among them, obesity is very common in PsA, with a prevalence of 27%, as confirmed by a recent Spanish work 2. Obesity in PsA has been associated with higher disease activity and a worse effectiveness of biologic treatment in PsA.…”
mentioning
confidence: 75%
“…As far as we are concerned, these are the first data about clinical response to secukinumab in obese patients with PsA. Obesity has been shown to promote the expansion of IL-17-producing T cells in adipose and peripheral tissues 6. In addition, in patients affected by metabolic syndrome, the levels of IL-17R expression in the liver or muscles are correlated with insulin resistance 6.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…In summary, there is sufficient evidence demonstrating the high prevalence of comorbidity [2,4,5] in patients with PsA and its impact on outcome measures, treatment response and clinical decision-making [6,[9][10][11][12][13]. A number of studies have also highlighted that comorbidity clearly impairs function and quality of life in PsA patients.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that more than half of patients with PsA have at least one comorbidity [2,3]. The most prevalent comorbidities associated with PsA are cardiovascular disease, metabolic syndrome, depression and anxiety, osteoporosis, ophthalmic, liver, kidney and inflammatory bowel disease [2,4,5].…”
mentioning
confidence: 99%